Using coalgebra and coinduction to define ontology-based multi-agent systems. (2nd March 2009) - Hadzic, Maja; Chang, Elizabeth
In the past, algebra has been predominantly used to define computer systems. However, computer systems are becoming more dynamic nowadays and algebra is not suitable any more to define such systems. For this reason, coalgebra and coinduction have been introduced into the computer and information society. Coalgebra and coinduction present a powerful mechanism for representing many different kinds of dynamic systems using a common formal framework. We make use of coinductive reasoning to provide a framework and define a dynamic process within the ontology-based multi-agent system. The principle is illustrated on a system specially designed to intelligently retrieve human disease information.